17. PENGARUH PENCELUPAN KARKAS AYAM PEDAGING DALAM LARUTAN ASAM SITRAT DAN ASAM ASETAT TERHADAP PENGHAMBATAN WAKTU PEMBUSUKAN The Immersion Effect of Broiler Carcass in Citric Acid and Acetic Acid On Spoilage Process Inhibition - Hilmiati H (Jurnal Medika Veterinaria, 2016)
The purpose of this research was to determine the immersion effect of chicken carcass in 3% citric acid, 3% acetic acid, and combination of 1.5% citric acid and 1.5% acetic acid on the spoilage time. A total of 36 broiler carcasses were divided into 4 treatment groups. The observation was conducted three times on 0, 4, and 8 hours. Broiler carcass in control group (K0) was without immersion in acid solution, while broiler carcass in first groups (K1), second groups (K2), and third groups (K3) were dipped in 3 % acetic acid, 3 % citric acid, and combination of 1.5 % acetic acid + 1.5 % citric acid, respectively. The data were analyzed using two way of analysis of variances. The average amount of spoilage chicken carcass in K0 vs K1 vs K2 vs K3 vs K4 on 0, 4, and 8 hours dipping were 0.0 vs 0.0 vs 0.0 vs 0.0, 1.0 vs 0.0 vs 0.33 vs 0.67, and 1.33 vs 1.33 vs 1.0 vs 1.33. The result showed that the immersion treatment was not significantly affect the spoilage time of the chicken carcass (P0.05), however the effect of treatment was significantly different between spoilage time (P0.05). The spoilage time were significantly differences (P0.05) between 0 and 4th hour (p= 0.008), 0 and 8th hour (p= 0.000), and 4th and 8th hour (p= 0.000). In conclusion, broiler carcass immersed in 3% acetic acid, 3% citric acid and their combination could inhibit spoilage time. ____________________________________________________________________________________________________________________ Key words: chicken carcass, citric acid 3%, acetic acid 3%, spoilage time